1999
DOI: 10.23986/afsci.5641
|View full text |Cite
|
Sign up to set email alerts
|

Cold hardiness research on agricultural and horticultural crops in Finland

Abstract: This paper represents an overview of cold hardiness research conducted on agricultural and horticultural crops, as well as on amenity plants in Finland. Inadequate freezing tolerance and/or winter hardiness often prevents introduction of new species and cultivars to Finland. Field observations on winter hardiness and more recently the results from laboratory freezing tests, have assisted breeders to select hardy genotypes. Research approaches for agricultural crops have evolved from observations on winter and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
(21 reference statements)
1
23
0
1
Order By: Relevance
“…Winters in the south-westernmost parts of Finland would be similar to those in Denmark. Although numerous factors affect success of overwintering capacity of field crops (Hömmö and Pulli 1993, Lindén et al 1999, Hofgaard et al 2003, Serenius et al 2005, Velicka et al 2006, considering mildness of winters only as a reduction in numbers of frost days, we can estimate the potential time-frame for introduction of currently grown autumn sown crops over a larger extent and introduction of novel overwintering crop species. For example, cultivation of winter wheat, currently grown only in restricted areas of southern Finland where there are about 130 frost days at most, can be extended to the Oulu region by end of this century in the A2 scenario (Fig.…”
Section: From Cold To Mild Winters and Consequent Estimated Introductmentioning
confidence: 99%
“…Winters in the south-westernmost parts of Finland would be similar to those in Denmark. Although numerous factors affect success of overwintering capacity of field crops (Hömmö and Pulli 1993, Lindén et al 1999, Hofgaard et al 2003, Serenius et al 2005, Velicka et al 2006, considering mildness of winters only as a reduction in numbers of frost days, we can estimate the potential time-frame for introduction of currently grown autumn sown crops over a larger extent and introduction of novel overwintering crop species. For example, cultivation of winter wheat, currently grown only in restricted areas of southern Finland where there are about 130 frost days at most, can be extended to the Oulu region by end of this century in the A2 scenario (Fig.…”
Section: From Cold To Mild Winters and Consequent Estimated Introductmentioning
confidence: 99%
“…In particular, knowledge about potential relationships between NAO and fungal infections in wheat during the winter period could further contribute to understanding of winter production security in different regions under a variety of climate conditions. In fact, for Finnish conditions it was concluded that breeding for snow conditions, including selection of plants with enhanced resistance to low temperature fungi, was an important factor leading to increased winter survival of wheat (Linden et al 1999). Comparisons of the results from this study with field observations indicate that factors other than low temperature stress also contribute to total winter wheat kill under Norwegian conditions.…”
Section: Discussionmentioning
confidence: 66%
“…Outre le bagage génétique, plusieurs facteurs environnementaux et culturaux peuvent influencer l'endurcissement et la tolérance au froid des végétaux : la longueur de la saison de croissance sur le rosier (Strelets et Zhuravlev 1986), les températures minimales observées à l'automne et en hiver, l'épaisseur du couvert de neige et les conditions de cultures (Lindén et al 1999) de même que l'âge des plants . Il serait très intéressant de reprendre cette étude avec des plants de divers âges pour vérifier si le potentiel d'endurcissement au froid peut augmenter avec l'âge sur ces rosiers.…”
Section: Resultsunclassified